Dialogic literary gatherings. Science, thrill and the best works of literature for all (Journal of Parents and Teachers, 2016)
Dialogic literary gathering is a cultural and educational activity, identified by the research project INCLUD-ED (2006-2011) as one of the successful educational actions that educational activities that contributes to decrease school failure. The school Sagrada Familia in Valencia has been implementing dialogic literary gatherings for 3 years, in early chidlhood, Primary and Secondary Education, in Castilian, valencian and english, reading the best works of literature. After its implementation, there has been an increase of awareness and meaning making for reading, and an improvement in coexistence in the school.
Keywords: Dialogic literary gatherings; reading; dialogue; learning; meaning making; coexistence.